Future of remote presence in developing countries and its applications in medicine (robot to otorob) - Muhammad Iftikhar Hanif; Muralindran Mariappan (International Association of Online Engineering Kirchengasse, 2010)
Mobile robots are expensive for developing and under developed countries. Their utilizations are general in field of medicine, from neurosurgery to intensive care units. Our ongoing project “OTOROB” which stands for Orthopedic Robot is more specific for the usage of orthopedic surgeons with special consideration on its cost effectiveness. Statistical analysis of the survey conducted helped to identify the requirement of orthopedic surgeons to make OTOROB more specific. A new concept of VIrtual Presence (VIP) Specialist Clinic and Roboscope are discussed.